Transsexualiteit: vreemdeling in eigen lichaam; juridische en medische opstellen - van der Reijt, F.A.; Pen, A.; Kirkels, V.G.H.J. (Zwolle: Tjeenk Willink, 1976)
"F.A. van der Reijt; A. Pen; V.G.H.J. Kirkel... et al. Fonds Suzan Daniel (FSD)"